Dentigerous Cyst Associated with an Impacted Maxillary Supernumerary Tooth: Life Sciences-Oral Pathology - Jason, Rebecca; Ananth, Neil; Lal, M S Jaish; Rani, T Sudha; Dinakar, J; Kumar, K U Goma; Libin, Selva (International Journal of Life Science and Pharma Research, 2022)
Dentigerous cysts are common cysts of the oral cavity and are said to arise, due to an accumulation of fluid between the reduced enamel epithelium of the dental follicle and the crown of the unerupted tooth. Their indolent behaviour warrants only surgical enucleation which is curative. The occurrence of dentigerous cysts in association with impacted supernumerary teeth accounts for 5% of the total cases, making it a rare phenomenon and raising considerable concerns due to the possible metaplastic and neoplastic transformations reported to arise from dentigerous cysts. Here we report a case of a 38-year-old male patient with a slow growing swelling in the anterior maxilla which was a radiographically seen as a unilocular radiolucency with no associated calcifications and hence prompted suspicions of a nasopalatine duct cyst which was contradicted on surgical enucleation which produced two small teeth like structures.